ISLAMIC BANKING PROFITABILITY IN FINANCING SUSTAINABLE PRIORITY SECTOR IN INDONESIA - Ayu Yuningsih; Romi Adetio Setiawan; Suharyono (Universitas Muhammadiyah Bengkulu, 2026)
This study examines the profitability potential of Islamic banking financing in sustainable economic sectors in Indonesia, particularly industries that implement environmental risk management. Although sustainable financing is a key component of Indonesia’s future economic development, its profitability remains a subject of debate. This research employs the Auto-Regressive Distributed Lag (ARDL) approach to analyze both short-run and long-run relationships between Islamic bank financing and priority sectors of sustainable finance. The study uses monthly time-series data from January 2014 to June 2025, comprising 138 observations. The findings indicate that financing in the manufacturing sector as well as the transportation, warehousing, and communication sectors has significant profitability potential for Islamic banks. However, the study is limited to Islamic banking institutions and requires additional variables to provide a more comprehensive analysis. Future research should utilize more specific bank-level time-series data to better represent the performance of commercial banks in Indonesia. Furthermore, the study recommends strengthening Indonesia’s legal and regulatory framework on sustainable finance taxonomy to establish clearer legal relationships and enhance regulatory certainty among stakeholders